planificacion de un programa instruccional piloto de metacognición con relacion a la expresion escrita dirigida a alumnos universitarios. - Bausela Herreras, Esperanza (Revista Complutense de Educación, 2003)
this article has a objetive to develop an intervention program, with object or intervening in relationship toward the metacognicion toward the writing directed to university pupil, leaving of a double premise, on one hand, we aer convinced that the metacognicion in relation to the writing con improve by means of the instruction and practice and, on the other hand, the development of all these abilities not always takes place in an autonomous way in the students it is,for it that the services psicopeddagogicos has a fundamental paper in the development of such programs.
Keywords: models of direction by programs; psicopedagogica direction; metacognicion in relation t the writing